The Ghost of Napoleon - Hart, Liddell (Rawalpindi, Pakistan Services Book Club, 1933)
The main historical theme of this book was set forth in the Less knowles Lectures for 1932-33 delivered at Trinity College, Cambridge, under the title----The Movement of Military Thought from the Eighteen to the Twentieth Century, and its influence on European history. The final chapter has been added subsequently, together with various interpolation in the earlier chapters.
Include Bibliographical notes and Index
Keywords: Military art and science -- War -- Napoleon I, Emperor of the French, 1769-1821 -- Military history, Modern